Influence of inlet air temperature and feed flow rate on the physical properties of spray-dried mengkudu (Morinda citrifolia) extract - Mohamad Yusof Maskat,; Yeow , Lee Ling (Universiti Kebangsaan Malaysia, 2004)
Due to the increase in consumer interest, mengkudu (Morinda citrifolia) extract is being produced in several forms including dry powder. One of the methods that can be used to produce dry powder is spray drying. This study was done to determine the physical properties of powdered mengkudu extract produced by spray drying from different sections of the spray-dryer. Mengkudu extract at 50% (v/v) dilution was spray-dried using two levels of feed flow rate (350 mL/hr and 475 mL/hr) and inlet air temperature (170oC and 190oC). Spray dried mengkudu extract from the cyclone and colletion sections of the spray dryer was collected and analyzed for amount produced, moisture content and colour. No significant interaction between feed flow rate and inlet air temperature used was observed for all parameters measured. Inlet temperature used did not show any significant effect on amount of production. However, increasing the inlet air temperature from 170oC to 190oC did produce lower moisture content for samples from the cyclone but no significant difference for samples from the collection bottle, while lowering the degree of redness of samples from the collection bottle, while lowering the degree of brightness for samples from both cyclone and collection sections of the spray-dryer. Feed flow rate used did not produce any significant effect on all parameters measured.